2021
DOI: 10.1002/slct.202004148
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Functionalized Silica‐Coated Magnetic Nanoparticles for an Efficient Suzuki Cross‐Coupling Reaction

Abstract: In this study, a new, efficient and inexpensive strategy has been developed based on the heterogeneous copper catalyst for the synthesis of different biaryl compounds via the Suzuki–Miyaura cross‐coupling reaction. In this respect, the core@shell modified Fe3O4@SiO2 magnetic nanoparticles (MNPs) has been prepared by immobilization of aminoguanidine and then the copper (II) ion into the surface of magnetic nanoparticles. After full characterization of the prepared catalyst by various technique such as TEM, SEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…It is worth noting that in the XRD pattern of Fe 3 O 4 @ SiO 2 -CT-Co, the diffraction peaks corresponding to cobalt ions have not been observed in the final catalyst, in agreement with the high cobalt dispersion [61]. The absence of Co diffraction peaks indicates the formation of finely dispersed cobalt species after immobilization on the surface of modified SiO 2 that are not detectable by this technique (as cobalt loading is lower than 5 wt% according to ICP results) [19,62,63].…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…It is worth noting that in the XRD pattern of Fe 3 O 4 @ SiO 2 -CT-Co, the diffraction peaks corresponding to cobalt ions have not been observed in the final catalyst, in agreement with the high cobalt dispersion [61]. The absence of Co diffraction peaks indicates the formation of finely dispersed cobalt species after immobilization on the surface of modified SiO 2 that are not detectable by this technique (as cobalt loading is lower than 5 wt% according to ICP results) [19,62,63].…”
Section: Resultssupporting
confidence: 69%
“…During the last decades, miscellaneous transition metal catalysts especially palladium-based catalysts have been used to construct various organic and bioorganic molecules via Suzuki-Miyaura cross-coupling reaction. Since palladium catalysts have some drawbacks like air sensitivity, high cost, and toxicity, efforts have been highly focused on designing effective transition metal catalysts including cobalt [14][15][16][17], copper [18][19][20], nickel [21][22][23], and zinc [24,25] instead of using catalysts based on expensive metals like palladium [26][27][28]. Among all of the transition metal catalysts used in carbon-carbon coupling reactions, cobalt has gained great attention due to its precious properties such as eco-friendly, low cost, nontoxicity, and good availability; therefore, many studies have shown the implementation of catalytic systems based on cobalt with the usage of various linkers in carbon-carbon coupling reactions [16,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pary et al described Cu 2 O nanoparticle-mediated oxidative C–C coupling reactions [ 25 ]. Sonei et al reported that Copper-functionalized silica-coated magnetic nanoparticles catalyst gives good to excellent yields at 80 °C in Suzuki-Miyuara cross-coupling reaction under solvent-free conditions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In organic synthesis, the Ullmann C-C homocoupling, C-N, and C-O hetero coupling reactions are essential tools to prepare the bi-aryl, di-aryl amine and di-aryl ether structures. These are analogues to many natural products and precursors in synthesizing many biologically active complexes [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%